Survey of Obstetrician-Gynecologists in the United States About Toxoplasmosis - Jeffrey L. Jones; Vance J. Dietz; Michael Power; Adriana Lopez; Marianna Wilson; Thomas R. Navin; Ronald Gibbs; Jay Schulkin (Hindawi Limited, 2001)
Background: Although the incidence of toxoplasmosis is low in the United States, up to 6000 congenital cases occur annually. In September 1998, the Centers for Disease Control and Prevention held a conference about toxoplasmosis; participants recommended a survey of the toxoplasmosis-related knowledge and practices of obstetrician-gynecologists and the development of professional educational materials for them.